Preparo de novos complexos de Ru(II) com ligantes mistos como agentes fotocitotóxicos - Ariane Carla Campos de Melo (2017)
One of the most important uses of metal compounds is in the treatment of cancer. The appearance of cellular resistance and the side effects associated to the known drugs have stimulated the search for new compounds. In this work, we have synthesized novel ternary complexes of Ru(II) with N-heterocyclic ligands. Eleven complexes of Ru(II) oftype [RuLL2]PF6, in which L = sulfamethizole (smz), sulfamethoxazole (smx), sulfasalazine (ssz), sulfamethoxypyridazine (smp), sulfapyridine (spd), or 2-thiophenecarboxylic acid hydrazide (shyd), L = 2,2-bipyridine (bpy) or 1,10-phenanthroline (phen) were prepared. The complexes were characterized by elemental and conductivity analyses, decomposition temperature, UV-vis, 1H NMR, and IR spectroscopies, electrospray ionization mass spectrometry (ESI-MS). The structures of[Ru(bpy)2smp](PF6) (1) and [Ru(phen)2smp](PF6) (2) were determined by single crystal X-ray diffraction. In all complexes, the geometry around the metal ion is a distorted octahedron. In the complexes with smz, smx, spd and smp, Ru(II) is coordinated to the sulfa via the sulfonamidic nitrogen and the nitrogen of the heterocyclic ring; in the complexes with ssz Ru(II) is coordinated to the carboxylate as a chelating ligand; and inthe complex with shyd via the terminal nitrogen and the carbonyl oxygen. Two heterocyclic nitrogens of the aa-diimines complete the coordination sphere. The interactions between the Ru (II) complexes and bovine serum albumin (BSA) were investigated by fluorescence spectroscopy at pH 7.3. The experimental data indicate that both complexes bind to BSA by a static mechanism. The complexes bind to BSA with binding constants ranging from 104 to 106. The effect of complexes in the growth of chronic myelogenous leukemia cells was investigated. All complexes exhibit significant cytotoxic activity and higher than those of the corresponding free ligands. The photocytotoxic activity of the complexes 1, 2 [Ru(bpy)2smz](PF6) (3), [Ru(phen)2smz](PF6) (4), [Ru(bpy)2ssz](PF6) (9) and [Ru(phen)2ssz](PF6) (10) was also investigated. UV-light exposure for 5 min increases cytotoxicity of all complexes, withan increase of approximately 100 times in the case of 2. Complexes 1 and 2 cleave supercoiled DNA after UV light irradiation but not in dark conditions. Complexes 1 and 2 bind to CT-DNA with the values of K = 2.8 × 104 mol L-1 and 2.5 × 105 mol L-1, respectively. Complexes 1, 2, 3, 4, 9 and 10 interact with the regulatory domain SH3 of the c-Abl protein, which is responsible for the development of chronic myeloid leukemia. The binding constants, determined by spectrofluorimetry, were 1.50 × 105,2.50 × 105, 9.78 × 103, 7.99 × 106, 4.16 × 104 and 4.02 × 105 L mol-1 for complexes 1, 2, 3, 4, 9 and 10, respectively. NMR studies of the interaction of complex 2 with the Abl-SH3 domain showed that the most affected residues were T79, G97, W99 and Y115.